MORPHOLOGICAL CHANGES IN THE BRONCHI IN CHILDREN AGED 5-6 YEARS - Sadikova Zumrad Shavkatovna; Bakieva Muhabbat Tursunkulovna; Khahhorova Madinaxon Azizovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: The respiratory system consists of the respiratory tract and two lungs. The airways are divided into the upper and lower respiratory tract, depending on their location in the body. The upper respiratory tract includes the nasal cavity, the nasal and oral part of the larynx, the lower respiratory tract include the hiccups, trachea (throat), bronchi, and lungs.he respiratory system consists of the respiratory tract and two lungs. The airways are divided into the upper and lower respiratory tract, depending.